2012
DOI: 10.1101/lm.026070.112
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of dopamine release deficits during object recognition memory acquisition attenuates cognitive impairment in a triple transgenic mice model of Alzheimer's disease

Abstract: Previous findings indicate that the acquisition and consolidation of recognition memory involves dopaminergic activity. Although dopamine deregulation has been observed in Alzheimer's disease (AD) patients, the dysfunction of this neurotransmitter has not been investigated in animal models of AD. The aim of this study was to assess, by in vivo microdialysis, cortical and hippocampal dopamine, norepinephrine, and glutamate release during the acquisition of object recognition memory (ORM) in 5-and 10-mo-old trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 61 publications
2
67
1
Order By: Relevance
“…Indeed, experimental data from transgenic mice AD showed how the DA-ergic pathology and amyloid deposition are closely related, suggesting a causative role for amyloid on dopamine dysfunction (Perez et al, 2005). Moreover, the restoration of DA transmission was demonstrated to play a role in memory and learning in a mouse model of AD, strengthening the central role of DA in cognitive tasks (Ambrée et al, 2009; Guzmán-Ramos et al, 2012). This has been recently associated to a demonstrated protective role, having DA an anti-amyloidogenic and anti-oxidant effects in mice brain (Himeno et al, 2011).…”
Section: Dopamine System In Alzheimer's Diseasementioning
confidence: 87%
“…Indeed, experimental data from transgenic mice AD showed how the DA-ergic pathology and amyloid deposition are closely related, suggesting a causative role for amyloid on dopamine dysfunction (Perez et al, 2005). Moreover, the restoration of DA transmission was demonstrated to play a role in memory and learning in a mouse model of AD, strengthening the central role of DA in cognitive tasks (Ambrée et al, 2009; Guzmán-Ramos et al, 2012). This has been recently associated to a demonstrated protective role, having DA an anti-amyloidogenic and anti-oxidant effects in mice brain (Himeno et al, 2011).…”
Section: Dopamine System In Alzheimer's Diseasementioning
confidence: 87%
“…The novel object and novel place recognition tasks are believed to be primarily dependent on both cortex and hippocampus, although the contributions of these two regions are distinct and dissociable. [54][55][56][57] Therefore, we analyzed AD-like pathology in the cortical and hippocampal regions of vaccinated mice with and without memory Th cells and control non-vaccinated mice. We observed that immunization with EV was effective in reducing AD-like pathology in the cortex but not in the hippocampus, and this effect depended on pre-existing Th cells ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] Accordingly, as a pre-clinical test of the therapeutic efficacy of EV vaccination, we studied neuropathological changes in the brains of aged Tg2576 mice (average 15-15.5 months old) possessing or not possessing the pre-existing memory Th cells prior to vaccinations. We tested numbers of 6E10 (diffuse and cored)-and ThS (cored)-positive plaques in the cortex and hippocampus of vaccinated mice with or without memory Th cells and the control adjuvant-only injected mice ( Figure 6).…”
Section: Vaccination With Ev Reduced Glial Activation Without Increasmentioning
confidence: 99%
“…Increased cortical DA release.has been demonstrated during a variety of cognitive behaviours in rodents, including cognitive behaviours (Giovannini et al, 1998;Phillips et al, 2004;Ihalainen et al, 2010;Guzmán-Ramos et al, 2012;Stanley et al, 2012) and in primates in a working memory task (Watanabe et al, 1997).…”
Section: Cortical and Hippocampal Da Release And Normentioning
confidence: 99%